Educational Potential of Cultural Traditions in the Modern Japanese Family Education - Nataliya Zbroуeva (Pedagogical Discourse, 2012)
This article analyzes the place and role of cultural traditions in Japanese family education, which plays a crucial educational role, exercising influence on the stages of maturity of the child, to form specific, socially expected of Japanese society traits.